PRIVATE SECURITY AND TRANSPORT OF MONEY AND OTHER VALUABLES IN FRANCE – HISTORICAL AND LEGAL ASPECTS (Heritage, 2024)
One of the challenges faced by most countries today is adopting an appropriate legal framework to regulate the most important issues of private security activities. Certainly, one of these issues is the services provided by private security companies, which include the activity of securing the transport of money and other valuables.France, as a member state of the European Union, has a specific legal framework. The subject of this paper is the analysis of the legal framework regulating private security activities concerning the transport of money and other valuables. In this regard, the historical development of the legal framework will be particularly analyzed. Additionally, the provisions of the current Code of Internal Security (Code de la sécurité intérieure) will be analyzed, which, among others, regulate the following issues: performing tasks of transportation of money and other valuables; conditions that transport vehicles must meet; types of transport vehicles; transport vehicle crew (wearing a uniform, protective vest and weapons) and technical protection systems.
Keywords: private security, transport of money and other valuables, cash-in-transit, legal framework, France.